SCREENING BRINJAL GENOTYPES FOR RESISTANCE TO SHOOT AND FRUIT BORER, LEUCINODES ORBONALIS AND ANALYSING THE GEOGRAPHIC DIVERGENCE OF RESISTANCE THROUGH DIVAGIS - K. RAMEASH,; N. SIVARAJ,; B SARATH BABU,; S. K. CHAKRABARTY, (The Bioscan, 2015)
Field screening of 52 brinjal (Solanum melongenaL.) genotypes, sourced from different regions of India covering 14 states, was carried out to evaluate their reaction to the shoot and fruit borer, Leucinodes orbonalis Guenee. Among the genotypes screened, four accessions viz., IC136347, IC127021, IC111077 and IC013332 were identified as resistant by recording a lower (<10 %) fruit damage, while seven genotypes as fairly resistant; 11 as tolerant; 20 as susceptible and 13 as highly susceptible to L. orbonalis. The correlation between morphological attributes and the shoot infestation showed that, the plant spread (r =0.592 at P < 0.01)and number of primary branches (r =0.404 at P < 0.01) had a significant positive correlation with the infestation of shoot and fruit borer. The DIVA-GIS analysis revealed that the germplasm collected from the states of Andhra Pradesh, Haryana, Jharkhand and Tripura were found to be having a higher Shannon diversity index (1.109 - 0.832) and coefficient of variation (35% - 60%) indicating a presence of wider range in sources of resistance for L. orbonalis in those regions. Targeted germplasm exploration in the identified areas would provide good sources of resistance in brinjal for L. orbonalis.